An investigation of the effects of coordinatio training on cognitive function in older adults - CREMEN, ISEULT ANNA (Trinity College Dublin. School of Psychology. Discipline of Psychology, 2018)
The world?s population is ageing. It is well known that the ageing process causes progressive loss of various cognitive functions and physical capacities. Modern neuroimaging techniques have shown that these changes are associated with structural brain changes. Diminished cognitive function in old age is not however universal. The actual loss of function differs greatly between individuals. The finding that neuroplasticity, the brain?s capacity for adaptive reorganisation and change, is retained in the ageing brain has inspired much research looking into methods to ameliorate cognitive decline amongst older adults. Research has shown that certain lifestyle factors are related to better cognitive health, such as level of education, socioeconomic status social engagement, habitual levels of physical activity, and occupational attainment. Of these factors, only a few are currently thought to be amenable to change in later life. As a consequence, a great deal of research over the past two decades has focussed on the use of interventions with a view to enhancing cognitive function in older adults, and preventing further decline. Cognitive training interventions that focus upon specific components of cognitive function have not lived up to their initial promise. In particular, there is little evidence that any derived benefits extend to capabilities that have not been trained directly. In this regard, physical activity interventions appear to have greater potential. Engaging in aerobic physical activity has been shown to provide benefits for the ageing brain; however, little is known about the underlying mechanisms subserving these benefits. There has been some recognition that multiple ?pathways? mediate the benefits for cognition that accrue from different types of physical activity. That which has been neglected to date is consideration of ?motor fitness? ? components of physical capability distinct from muscle strength and cardiovascular capacity ? which are linked to the retention of cognitive function. In this regard, associations have been shown between executive function and key elements of motor fitness, such as movement speed, balance, and motor coordination. The factors that account for the generalised effects of motor fitness on cognitive function are not currently understood, and have not yet been examined in detail. In order to exploit its therapeutic potential, this deficiency must be addressed. The purpose of the present work is to explore the effects of motor coordination training on the executive functions of older adults. Chapter 1 is a review of the literature that provides the theoretical basis for the experimental work reported in this thesis. The latter comprises two blinded randomised controlled trials that explore the impact of two variants of motor coordination training on the cognitive function of older adults. In the first study (Chapter 2), twenty healthy older adults trained individually on a unilateral centre-out target acquisition task in five sessions conducted over one week. A second group of twenty participants were engaged in an active control task. Executive functions were assessed prior to training, post-intervention and at a retention session conducted ten days following the post-test. Individuals who engaged in the motor training task exhibited improvements on a subset of the cognitive tasks, including the Choice Reaction Time task and components of the Dual n-Back task. These improvements in performance were not exhibited by individuals who engaged in an active control task. In addition, all participants carried out a visuomotor task at the pre- and post-intervention sessions. Individuals who were engaged in the motor training task exhibited improved performance on the visuomotor task post-intervention, in terms of decreased movement time and lower path deviation, whereas these effects were not observed for control group participants. In addition, interlimb transfer from the trained limb to the untrained limb was observed on the baseline motor task post-intervention for the training group only, indicating that neural adaptation to the motor task occurred. However, no association was found between individual degree of adaptation to the baseline motor task and the degree of improvement on the cognitive measures. In the second trial (Chapter 3) thirty older adults were trained individually on a different variant of the target acquisition task in which the visual feedback was deferred, A second group of thirty participants were engaged in an active control task. Provision of post-trial feedback is thought to engender ?explicit? learning strategies in task adaptation. Individuals who were engaged in the motor training task exhibited improved performance on components of the Wisconsin Card Sorting Task (WCST). In addition, all participants carried out a visuomotor task at the pre- and post-intervention sessions. Individuals who were engaged in the motor training task exhibited differences in performance on the visuomotor task at the post-intervention session, showing decreased velocity and later time at peak velocity at the post-test, and lower path deviation at the retention session, whereas these effects were not observed for control group participants. In addition, interlimb transfer from the trained limb to the untrained limb was observed in performance on the visuomotor task at post-intervention for the motor training group only, providing additional evidence that neural adaptation to the motor task occurred. In addition, these participants showed a degree of improvement on the Trail Making Task and the Mental Rotation Task. A statistical relationship was found between the degree of adaptation to the visuomotor task at the post-intervention session and the number of Conceptual Level Responses on the WCST. This suggests common mediation of the alterations in motor control that were brought about through repetition of the coordination training task, and the gains in cognitive function that were observed following the cessation of training. Finally, Chapter 4 provides a discussion of the findings and their implications, along with future challenges in this avenue of research. In general summary, the results of the randomised controlled interventions described herein support the proposition that motor training can lead to positive transfer of functional capacity to the cognitive domain.
APPROVED